Kinerja Keuangan dengan Metode Economic Value Added (EVA) : Studi Pada PT Kimia Farma, Tbk. Yang Terdaftar Di BEI Tahun 2018-2022 - Sepbeariska Manurung (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Performance of the company is mostly measured by financial ratio for a spesific period. This measurement must be in accordance with generally accepted accounting treatment in preparing financial statements. Financial ratios have weaknesses in measuring performance where performance looks good but does not increase or even decrease. Therefor, other measuring are needed that can show the success of the company with the aim of adding economic value. Economic Value Added (EVA) is one of the most relevant measurements in measuring a company's financial performance because it can show how much added value can be generated during a spesific period.This research using qualitative descriptive method with secondary data from financial statement of PT Kimia Farma, Tbk listed on Indonesia Stock Exchange for 2018-2022. This study aims to find out the financial performance of PT Kimia Farma, Tbk listed on the BEI using the Economic Value Added (EVA) method. Economic value added (EVA) is an added value for the company by incurring capital costs. The result of this research indicate that financial perform with EVA method are negative, means that it performs is not optimal.